Violent rituals of the Hebrew Bible - Olyan, Saul M. (Oxford University Press, 2019)
Ritual violence prescribed -- Violent rites narrated -- Ritual violence envisioned -- Ritual inversion and mitigating rites -- The role of circumstantially dependent rites in ritual violence -- The social dimensions of ritual violence.